Cost-effective evaluation and management of cranial neuropathy - Babu, Seilesh; Jackson, Neal M. (Thieme, 2020)
"This textbook is the result of many conversations around the country in clinics, on hospital rounds, and at professional conferences. Patients with cranial neuropathy can be clinically challenging. Sometimes a missed diagnosis can be life threatening. Nowadays more and more payers, such as governments and insurance companies, are concerned with cost effectiveness of diagnostic and treatment steps. Therefore, physicians are often put in a challenging position between being good stewards of financial resources and being good providers of quality medical care. As the reader will observe in the subsequent chapters, cranial nerve issues are inherently complex and require expert clinical and radiographic evaluation. The primary aim of this textbook is to guide clinicians during these difficult situations"--